Dizionario gramsciano / Gramsci Dictionary: Modern Prince - La Porta, Lelio (International Gramsci Journal, 2023)
This is an English-language translation of Lelio La Porta’s entry on the “Modern Prince” in the Dizionario gramsciano (ed. G. Liguori and P. Voza, Roma: Carocci 2007).